Strengthening The "Mampesendong" Food Processed MSME Business in Malang City Through Business Management Assistance - Sunyoto, Agus Bambang; Antara, Raditya M; Hermawan, Agus; Winarno, Agung (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
National economic stability can be maintained through the existence of Micro, Small, and Medium Enterprises (MSMEs) which have a central role in expanding employment and improving people's welfare. The purpose of this service activity is to strengthen the business capacity of "Mampesendong" Processed Food MSMEs with a focus on improving managerial skills and business assistance. This assistance is intended to create sustainable and highly competitive operations. These efforts are carried out in a planned and sustainable manner with the goal of increasing productivity, creating new entrepreneurs, and improving community welfare. The implementation process includes problem identification, needs analysis, program implementation, mentoring, and evaluation. Through this approach, the service team developed four main programs, namely: (1) digital financial statement management training, (2) strengthening attractiveness through graphic design, (3) developing online and offline marketing strategies, and (4) product innovation to increase competitiveness.